Photo-enhanced toxicity of undispersed and dispersed weathered Macondo crude oil to Pacific (Crassostrea gigas) and eastern oyster (Crassostrea virginica) larvae. (August 2018) - Finch, Bryson E.; Stefansson, Emily S.; Langdon, Chris J.; Pargee, Suzanne M.; Stubblefield, William A.
Abstract: During the Deepwater Horizon oil spill rapid natural weathering of Macondo crude oil occurred during the transport of oil to coastal areas. In response to the DWH incident, dispersant was applied to Macondo crude oil to reduce the movement of oil to coastal regions. This study aimed to assess the narcotic and phototoxicity of water-accommodated fractions (WAFs) of weathered Macondo crude oil, and chemically-enhanced WAFs of Corexit 9500 to Pacific ( Crassostrea gigas ) and eastern ( Crassostrea virginica ) oyster larvae. Phototoxic effects were observed for larval Pacific oysters exposed to combinations of oil and dispersant, but not for oil alone. Phototoxic effects were observed for larval eastern oysters exposed to oil alone and combinations of oil and dispersant. Corexit 9500 did not exhibit phototoxicity but resulted in significant narcotic toxicity for Pacific oysters. Oyster larvae may have experienced reduced survival and/or abnormal development if reproduction coincided with exposures to oil or dispersant. Highlights: Early life stages of oyster larvae are sensitive to phototoxic effects of Macondo crude oil when exposed to ambient sunlight. Dispersed Macondo oil was more phototoxic to oyster larvae compared with undispersed oil. Eastern oyster larvae were more sensitive to phototoxicity of Macondo oil compared to Pacific oyster larvae. Corexit 9500 did not exhibit phototoxic effects to oyster larvae.